Neuropathological profile of long‐duration amyotrophic lateral sclerosis in military Veterans. (4th August 2020) - Spencer, Keith R.; Foster, Zachariah W.; Rauf, Nazifa Abdul; Guilderson, Latease; Collins, Derek; Averill, James G.; Walker, Sean E.; Robey, Ian; Cherry, Jonathan D.; Alvarez, Victor E.; Huber, Bertrand R.; McKee, Ann C.; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder affecting both the upper and lower motor neurons. Although ALS typically leads to death within 3 to 5 years after initial symptom onset, approximately 10% of patients with ALS live more than 10 years after symptom onset. We set out to determine similarities and differences in clinical presentation and neuropathology in persons with ALS with long vs. those with standard duration. Participants were United States military Veterans with a pathologically confirmed diagnosis of ALS (n = 179), dichotomized into standard duration (<10 years) and long‐duration (≥10 years). The ALS Functional Rating Scale‐Revised (ALSFRS‐R) was administered at study entry and semi‐annually thereafter until death. Microglial density was determined in a subset of participants. long‐duration ALS occurred in 76 participants (42%) with a mean disease duration of 16.3 years (min/max = 10.1/42.2). Participants with long‐duration ALS were younger at disease onset ( P  = 0.002), had a slower initial ALS symptom progression on the ALSFRS‐R ( P  < 0.001) and took longer to diagnose ( P  < 0.002) than standard duration ALS. Pathologically, long‐duration ALS was associated with less frequent TDP‐43 pathology ( P  < 0.001). Upper motor neuron degeneration was similar; however, long‐duration ALS participants had less severe lower motor neuron degeneration at death ( P  < 0.001). In addition, the density of microglia was decreased in the corticospinal tract ( P  = 0.017) and spinal cord anterior horn ( P  = 0.009) in long‐duration ALS. Notably, many neuropathological markers of ALS were similar between the standard and long‐duration groups and there was no difference in the frequency of known ALS genetic mutations. These findings suggest that the lower motor neuron system is relatively spared in long‐duration ALS and that pathological progression is likely slowed by as yet unknown genetic and environmental modifiers.